Efficacy of combination therapy with pembrolizumab and axitinib for metastatic renal collecting duct cell carcinoma: A report on two cases. Issue 6 (26th September 2022) - Tamada, Shinji; Ikarashi, Daiki; Tsuyukubo, Takashi; Iwasaki, Kazuhiro; Isurugi, Kazumasa; Ono, Sadahide; Takata, Ryo; Fujisawa, Hiromitsu; Obara, Wataru
Abstract : Introduction: Immunotherapy‐based combinations have become the standard first‐line therapy for metastatic renal cell carcinoma. However, combined immunotherapy for renal collecting duct carcinoma had been reported, but its therapeutic efficacy had been unclear. Case presentation: The first case was a 62‐year‐old man treated with pembrolizumab and axitinib for renal collecting duct carcinoma with multiple bone metastases. After 7 months, the primary and metastatic lesions shrunk and were evaluated as a partial response. The second case was a 71‐year‐old man treated with pembrolizumab and axitinib for renal collecting duct carcinoma with lymph node and lung metastases. After 9 months, the primary and metastatic lesions shrunk and were evaluated as a partial response. In both cases, the tumor cell expression of programmed death ligand‐1 was negative, and CD4 + and CD8 + cells were observed in the tumor. Conclusion: Combined immunotherapy with pembrolizumab and axitinib may be effective for metastatic renal collecting duct carcinoma.